2015
DOI: 10.1124/jpet.114.220665
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Metabolite Compound K Suppresses T-Cell Priming via Modulation of Dendritic Cell Trafficking and Costimulatory Signals, Resulting in Alleviation of Collagen-Induced Arthritis

Abstract: Ginsenoside metabolite compound K (CK; 20-O-D-glucopyranosyl-20(S)-protopanaxadiol), a novel ginsenoside metabolite, belongs to the dammarane-type triterpene saponins, according to its structure. The anti-inflammatory activity of CK has been identified in several studies. Our study demonstrated that CK exerted an anti-inflammatory effect in collagen-induced arthritis (CIA) and adjuvant-induced arthritis animal models, and this effect was due to inhibition of the abnormal activation and differentiation of T cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 45 publications
2
32
0
Order By: Relevance
“…In addition, CK decreased the percentage of activated T-cell subsets such as CD4 þ CD154 þ T and CD4 þ CD69 þ T, and increased the percentage of naive T-cells (CD4 þCD62Lþ ) of spleen . CK relieved the excessive T cells activation by suppressing signals provided by CD80/CD86-CD28, MHCII-TCR and CD25-IL-2 (Chen et al, 2015). And these studies also demonstrated that CK exerted anti-arthritis effect in AA and CIA.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…In addition, CK decreased the percentage of activated T-cell subsets such as CD4 þ CD154 þ T and CD4 þ CD69 þ T, and increased the percentage of naive T-cells (CD4 þCD62Lþ ) of spleen . CK relieved the excessive T cells activation by suppressing signals provided by CD80/CD86-CD28, MHCII-TCR and CD25-IL-2 (Chen et al, 2015). And these studies also demonstrated that CK exerted anti-arthritis effect in AA and CIA.…”
Section: Introductionmentioning
confidence: 85%
“…CK possesses several pharmacological activities including antitumor, anti-inflammatory and anti-allergic action (Helliwell et al, 2015;Radad et al, 2011). Our previous studies demonstrated that CK played their anti-inflammatory and immunoregulatory effect in collagen-induced arthritis (CIA) and adjuvant arthritis (AA) by inhibiting abnormal T cells activation and differentiation (Chen et al, , 2015Wu et al, 2014;Liu et al, 2014). CK suppressed T cells proliferation in vivo and in vitro.…”
Section: Introductionmentioning
confidence: 98%
“…Ginsenoside compound K (CK), the primary deglycosyl metabolite of ginsenosides produced under the action of intestinal flora and absorbed into the body, has been proven to elicit anticancer, anti-inflammatory, anti-allergic, antidiabetic, anti-angiogenic, anti-aging, neuroprotective, and liver protective properties among several notable biological characteristics [2]. Ginsenoside CK is a rare ginsenoside derived from ginseng saponins Rb1 and Rb2 by intestinal bacteria [3]. The method of synthesis of CK has garnered significant attention.…”
Section: Introductionmentioning
confidence: 99%
“…Ginsenoside compound K (CK), or 20-O-β-(D-glucopyranosyl)-20(S)-protopanaxadiol (The molecular structure is shown in Fig 1 ), is naturally absent. It belongs to the rare ginsenoside, which is transformed from ginsenosideRb1 and Rb2 by intestinal bacteria [ 5 ]. Ginsenosides are poorly absorbed from the gut while their metabolite CK is absorbed.…”
Section: Introductionmentioning
confidence: 99%